Nonstationary Parametric Amplification of Polychromatic Radiation Propagating in an Extended Absorbing Resonant Medium - Bagaev, SN; Egorov, V; Mekhov, I; Moroshkin, P; Chekhonin, I; Davlyatshin, E; Kindel, E (2003)
Amplification spectra for an optically dense resonator extended medium interacting with two-wave polychromatic laser radiation was performed. It was shown that, depending on the pumping power, its spectral composition and the characteristics of the medium, different field-substance interaction regimes were realized. The results showed that the amplification spectra of an optically dense medium reproduced all types of spectra inherent to the effect of so-called condensation of an oscillation spectrum under intracavity pumping of an optically dense medium.